The Effect of Wearing N95 Respirator Masks on Intraocular Pressure of Health Care Workers - Denise Patricia M. Granada, MD; Paolo S. Silva, MD; Rainier Victor A. Covar, MD, MMed (Philippine Journal of Ophthalmology)
Objective: We determined if there was a significant change in the intraocular pressure (IOP) of healthcare workers with extended use of N95 masks.